THE LEARNING MODEL ANALOGY IN IMPROVING THE MULTICULTURAL WRITING CREATIVITY - SAKDIAH WATI (Sriwijaya University Learning and Education International Conference, 2016)
The learning model analogy in linguistics was the similarities between the forms which became thebasis of other forms. Analogy was one of the morphology processes, where there was a formulation ofthe new words from the existed word. Analogy was done because from something that has beencompared and its comparation has the same function and role. By doing analogy, a person couldexplain something which was abstract or complicated to be something that easy to be understood(inductive and logic analogy). Multicultural was a term that used to describe someone’s point of viewabout the life on this earth, or the policy which focused on different culture acceptance, citizen,system, culture, customs, and politics they have. At least, main thing that need to be planted by themwas done by teacher or lecturer, will be disturb by the literature management, finding information,practice the dialogue, and create a creative outside and multicultural. This study was qualitativeresearch, which had to test the language learning model affectivity. The objective of this study was tocreate creative multicultural learning method. In order to reach the objective, the method used in thisstudy was research and development system from Gall and Borg (2003). The specific target of thisresearch was the learning method, analogy. For all the students of Bahasa Indonesia study program insome university in Palembang with this specification : (1) the objective of learning based oncurriculum 2013; (2). Could be done with or without the lecturer; and (3 ) could develop creativelearning for students. Based on the method , (1) teaching and learning observation in quasyexperiment classroom. (2) selecting short story to be a material for teaching; (3). Learning modelcomposition; (4) learning models tested; (5). Result evaluation; and (6). Learning model revision